Corticosteroid-Induced Sinus Bradycardia in a Dog with Systemic Lupus Erythematosus: A Case Report - Fang-Chi Tsou; Eng-Wen Lim; Pin-Guang Jann; Pin-Chen Liu (Animals)
A 3-year-old, 10.2 kg, spayed, female mixed-breed dog was diagnosed with systemic lupus erythematosus. The patient was administered intravenous methylprednisolone at a dose of 2 mg/kg twice daily. Over the next 24 h, the dog’s heart rate dropped to 42–48 bpm, while other vital signs remained stable. A 12-lead electrocardiogram revealed sinus bradycardia without any other arrhythmia. Notably, the dog was not receiving any beta-blockers or undergoing other therapies commonly associated with sinus bradycardia. After tapering the corticosteroid dose, no further episodes of bradycardia were observed. Herein, we report the first case of sinus bradycardia in a dog following intravenous methylprednisolone therapy to improve veterinarians’ understanding of corticosteroid-induced cardiac arrhythmias.